2009
DOI: 10.1051/0004-6361/200912664
|View full text |Cite
|
Sign up to set email alerts
|

How skeletons turn into quasi-separatrix layers in source models

Abstract: Context. In situations where there are no magnetic null points located above a reference photospheric plane, and when the photospheric magnetic field is modeled by discrete flux concentrations, the magnetic connectivity is defined by the magnetic skeleton of the configuration. For a continuous distribution of non-zero photospheric flux, the connectivity is defined by quasi-separatrix layers (QSLs). Both the magnetic skeleton and QSLs can account for current sheet formation and dissipation. Observationally, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…a vertical plane crossing the center of the red field lines in the figure. Since the second eigenvalue (-0.3) for the fan plane is much smaller compared to the first (-1.7), the field lines tend to follow the direction of −0.98, −0.18, −0.01 (red lines in the horizontal direction) rather than the vertical direction 0, 0, 1 (Restante et al 2009). Actually, if the last eigenvalue vanishes, the 3D null point simply equals 2D X-point where no field lines extend in the vertical direction.…”
Section: The Field Structure -Mhd Simulation Resultsmentioning
confidence: 99%
“…a vertical plane crossing the center of the red field lines in the figure. Since the second eigenvalue (-0.3) for the fan plane is much smaller compared to the first (-1.7), the field lines tend to follow the direction of −0.98, −0.18, −0.01 (red lines in the horizontal direction) rather than the vertical direction 0, 0, 1 (Restante et al 2009). Actually, if the last eigenvalue vanishes, the 3D null point simply equals 2D X-point where no field lines extend in the vertical direction.…”
Section: The Field Structure -Mhd Simulation Resultsmentioning
confidence: 99%
“…Since then, investigating the locations of QSLs has proved to be successful at interpreting a large variety of flaring regions (e.g. Schmieder et al 1997;Bagalá et al 2000;Mandrini et al 2006;Restante, Aulanier & Parnell 2009;Chandra et al 2011).…”
Section: Qsls In the Presence Of Flux Ropes: From Theory To Observationsmentioning
confidence: 99%
“…In this context, Priest & Forbes (1992) have first shown that the behavior of 2.5D magnetic field lines, reconnecting at a 2D X-point with a finite guide field perpendicular to the plane of the X-shaped separatrices, was different from standard separatrix reconnection: they argued in favor of a continuous flippage of the field lines across the remnants of the separatrices, instead of a classical cut-and-paste reconnection. Quasi-separatrix layers (QSLs), which are narrow volumes across which the magnetic field connectivity changes drastically, but in a continuous way, have then been developped as a likely geometrical extension of 2.5D flipping layers, and of 3D separatrices found in classical source models (Priest & Démoulin 1995;Démoulin et al 1996a;Restante et al 2009). …”
Section: G Aulaniermentioning
confidence: 99%